2003
DOI: 10.1074/jbc.m210287200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Internal Ribosome Entry Site-mediated Translation Is Stimulated by Specific Interaction of Independent Regions of Human La Autoantigen

Abstract: The human La autoantigen has been shown to interact with the internal ribosome entry site (IRES) of hepatitis C virus (HCV) in vitro. Using a yeast three-hybrid system, we demonstrated that, in addition to full-length La protein, both N-and C-terminal halves were able to interact with HCV IRES in vivo. The exogenous addition of purified full-length and truncated La proteins in rabbit reticulocyte lysate showed dose-dependent stimulation of HCV IRES-mediated translation. However, an additive effect was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 62 publications
8
89
1
1
Order By: Relevance
“…Many of the viral RNAs interacting with La protein also contain a close match or exact CACAA sequence (Ali et al, 2000). For example, La protein interacts with the HCV 59 NCR with a GCAC sequence (Pudi et al, 2003). The toe-printing experiments described here indicated that La protein interacted with sequence ACA (nt 10929-10931) in loop I of the JEV 39 SL RNA, whilst it bound to sequence AAG (nt 10940-10942) in loop II.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Many of the viral RNAs interacting with La protein also contain a close match or exact CACAA sequence (Ali et al, 2000). For example, La protein interacts with the HCV 59 NCR with a GCAC sequence (Pudi et al, 2003). The toe-printing experiments described here indicated that La protein interacted with sequence ACA (nt 10929-10931) in loop I of the JEV 39 SL RNA, whilst it bound to sequence AAG (nt 10940-10942) in loop II.…”
Section: Discussionmentioning
confidence: 93%
“…La protein contains three RRMs: RRM1 and RRM2 are located in the N-terminal half of the protein, whilst RRM3 is located in the C-terminal half. The N-terminal domain of La protein has been shown to interact with the poliovirus 59 NCR (Izumi et al, 2004;Svitkin et al, 1994), whilst the C-terminal domain interacts with the HCV 59 NCR in vitro (Ali et al, 2000); however, both Nand C-terminal halves are able to interact with the viral RNA independently in vivo (Pudi et al, 2003). We have shown that La protein interaction with the JEV 39 NCR involves its N-terminal half only.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Since the mechanism of ribosome assembly is unique and fundamentally different from the cap-dependent translation of the host cell mRNA, it can be targeted to selectively inhibit viral protein synthesis and consequently its replication (Dasgupta et al, 2004;Hellen & Sarnow, 2001;Trowbridge & Gowans, 1998). Previously, we have demonstrated the importance of the GCAC sequence near the iAUG for ribosome assembly onto HCV IRES RNA (Pudi et al, 2003(Pudi et al, , 2005. In fact, human La protein (an important host factor) has been shown to bind to the above sites and a peptide derived from the RNA-binding region of La protein has been shown to interfere with the ribosome assembly and inhibit viral RNA translation (Ali et al, 2000;Mondal et al, 2008;Pudi et al, 2004Pudi et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%